Efficacy of Ebola Glycoprotein-Specific Equine Polyclonal Antibody Product Against Lethal Ebola Virus Infection in Guinea Pigs. (27th June 2018) - Chan, Mable; Holtsberg, Frederick W; Vu, Hong; Howell, Katie A; Leung, Anders; Van der Hart, Evelyn; Walz, Paul H; Aman, M Javad; Kodihalli, Shantha; Kobasa, Darwyn
Abstract: Background: Filoviruses including Ebola, Sudan, and other species are emerging zoonotic pathogens representing a significant public health concern with high outbreak potential, and they remain a potential bioterrorism-related threat. We have developed a despeciated equine Ebola polyclonal antibody (E-EIG) postexposure treatment against Ebola virus (EBOV) and evaluated its efficacy in the guinea pig model of EBOV infection. Methods: Guinea pigs were infected with guinea pig-adapted EBOV (Mayinga strain) and treated with various dose levels of E-EIG (20–100 mg/kg) twice daily for 6 days starting at 24 h postinfection. The E-EIG was also assessed for neutralization activity against related filoviruses including EBOV strains Mayinga, Kikwit, and Makona and the Bundibugyo and Taï Forest ebolavirus species. Results: Treatment with E-EIG conferred 83% to 100% protection in guinea pigs. The results demonstrated a comparable neutralization activity (range, 1:512–1:896) of E-EIG against all tested strains, suggesting the potential for cross-protection with the polyclonal antibody therapeutic. Conclusions: This study showed that equine-derived polyclonal antibodies are efficacious against lethal EBOV disease in a relevant animal model. Furthermore, the studies support the utility of the equine antibody platform for the rapid production of a therapeutic product in the event of an outbreak by a filovirus or other zoonotic pathogen.